OCENA PRIMENE ANAEROBNO DIGESTOVANE KANALIZACIJE NA GRANICE KONZISTENTNOSTI I KARAKTERISTIKE KOMPAKCIJE RAZLIČITIH TEKSTURA TLA - AKSAKAL, Ekrem Lutfi; CAMBAZTEPE, Armagan; ANGIN, Ilker; SARI, Serdar (Journal of Agricultural Sciences (Belgrade), 2024)
Notwithstanding its beneficial characteristics, agricultural utilization of organic wastes may have an adverse effect on soil properties if used improperly. To evaluate proper use, a laboratory study was conducted to investigate the effects of different sewage sludge application doses (0, 2, 4, and 8% weight/weight) on consistency limits and the compaction characteristics of three different textured soils. Application of sewage sludge significantly improved the consistency limits and reduced compactibility. The efficacy was depended on the amount applied. The rates of increase in liquid limit (LL) values at 8% sewage sludge were found as 58.7% for sandy loam, 43.4% for loam, and 16.2% for clay soil. As the application dose increased, the optimum moisture content (OMC) values increased and the maximum dry bulk density (MBD) values decreased. The highest application dose decreased the MBD by 9.5% in sandy loam, 6.5% in loam, and 13.7% in clay-textured soils. The rates of increase in OMC values were found as 73.4%, 53.8%, and 27.1%, for sandy loam, loam, and clay, respectively. Increasing the water content at OMC over LL and PL have demonstrated that soils can be tilled more easily in higher moisture contents without any degradation if properly mixed with sewage sludge.